2016
DOI: 10.1007/s40124-016-0099-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Uses for Three-Dimensional Printing in Congenital Heart Disease

Abstract: Congenital heart disease affects 1-2 % of the world's population and is the leading cause of mortality among infants in the US. The diagnosis and management of congenital heart disease are largely driven by review of two-dimensional (2D) images derived from echocardiography, cardiac magnetic resonance, and cardiac computed tomography. However, congenital heart disease is a threedimensional (3D) problem, and 2D display methods often lack critical spatial information. Cardiologists and cardiovascular surgeons re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…For 3D echocardiogram datasets, low-gain acquisitions and post-processing filtering to remove speckling noise is required [ 20 ]. Additionally, 3D reconstructions should be optimized by manually segmenting respective atria, ventricles and great vessels as separate masks (with clear definition of the ventricular septal defect between masks) [ 10 ] and reconstructing the heart via Boolean function. Typically, software segmentation takes approximately 2 h for each model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For 3D echocardiogram datasets, low-gain acquisitions and post-processing filtering to remove speckling noise is required [ 20 ]. Additionally, 3D reconstructions should be optimized by manually segmenting respective atria, ventricles and great vessels as separate masks (with clear definition of the ventricular septal defect between masks) [ 10 ] and reconstructing the heart via Boolean function. Typically, software segmentation takes approximately 2 h for each model.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should examine the impact of models on teaching CHD that are more complex and elaborate, such as hypoplastic left heart syndrome. This critical CHD requires multiple surgeries with anatomic variation after each surgery, such that learners are faced with learning four different anatomies instead of just one [ 10 ]. Feedback forms will include questions related to the “most favorite model” in order to investigate the effectiveness in 3D models’ ability to communicate spatial information (and relevant anatomical details in CHD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, 3D printed models have better spatial and structural visualization and can be used as didactic tools for better understanding of complex heart or vessel anatomy as well as easier explanation of abnormal anatomical heart and vessel structures. Some previous studies have shown its effectiveness of using 3D-printed models in CHD curriculum [ 11 , 18 , 19 ]. However, no controlled study with objective evaluation methods has ever been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, additively manufactured models have been introduced into cardiology, especially concerning the teaching of congenital heart disease affected 1–2% of the world’s population and being the leading cause of mortality among infants in the US. These pediatric models have tremendous educational value, demonstrate complex anatomical concepts such as double-outlet right ventricle, malalignment-type ventricular septal defects and the spectrum of heterotaxy syndromes ( 86 ).…”
Section: (Bio)medical Applicationsmentioning
confidence: 99%